Essence of Daylight in the Cistercian Monastic Church of S. Bento de Cástris, Évora, Portugal - Martins, Ana Maria Tavares (2020)
Natural light in the Cistercian churches is closely linked not only with the liturgical requirements at the “officium” but also with the canonical hours based on the "ora et labora" dictated by the Rule of St. Benedict. The Cistercian architecture, in its beginnings (12th century forward) is characterized by austerity, simplicity and the play of light and shadow that gives value to the monastic architectural space itself, making it perfect for a contemplative experience. In the Cistercian Monastery the church is the central piece of the monastic building. Nave, transept and apse are the main architectural components to which is added the choir. This paper contextualizes the importance and close connections of natural light, within the Cistercian Monasteries architecture. Thus the essence of daylight is analyzed within the Church of the Monastery of S. Bento de Cástris, in Évora, Portugal. This former Monastery (13th - 19th centuries) includes the church, at the southeastern corner which has not only a high choir, but also a low lateral choir (within the presbytery). Its unchanged exterior walls are made of solid masonry. Although the function of the walls is primarily structural, the windows allow the daylight to penetrate the space of the church. The church has two external façades facing northeast and southeast. The combined orientation effect of the church’s main axis and the sun trajectory determines how the sunlight reaches the interior of this architectural structure. This study presents the qualitative and quantitative analysis of the luminous environment in the church of S. Bento de Cástris, being the first based on the authors’ perception of the effect of the daylight within the different areas of the enclosed space. The appreciation of the spatial experiences was supported by quantitative daylight simulations that were conducted in selected areas within the space. With this paper is intended to contribute to the debate about the specificity of daylight, in the context of Cistercian architecture.